Experimental & numerical study on sheet metal lateral bending with both ends pinned - Mohd Adzlan, Mohd Azmi (2012)
The main aim of this study is to compare the buckling phenomenon of metal strip under both ends pinned setting. Buckling may be demonstrated by pressing the opposite edge of a plate toward one another. In achieving the objective, this research involves design and fabrication of the buckling test rig, run the experiment on test rig under condition both ends are pinned and to compare the experimental result with computer simulation. This thesis describes the methods of designing, fabricating and experiment the lateral bending test equipment. Started with test rig design, it has been developed. using SOLIDWORKS 2011.It is continued with fabrication work in FKM laboratory. Specific for the pinned ends design, V shape feature has been adopted in the design using a rectangular aluminum. The next stage is on experimental work, where the tests have been conducted as the planned test loading. The specimen showed buckling phenomenon and strain has been measured using the strain gauge connected to data logger system. The value of strain from experimental will be compare with strain values from ABAQUS simulation. From this project, we can prove that the experimental result is same with the simulation result.